Altered synchrony and loss of consciousness during frontal lobe seizures. Issue 2 (February 2016) - Bonini, Francesca; Lambert, Isabelle; Wendling, Fabrice; McGonigal, Aileen; Bartolomei, Fabrice
Highlights: This study investigated loss of consciousness in 52 frontal seizures. Interdependencies between signals were estimated by using non-linear regression analysis. Loss of consciousness appears to be related to changes in synchrony in prefrontal and parietal associative cortices. Abstract: Objective: Loss of consciousness (LOC) in frontal lobe epilepsy (FLE) has been rarely specifically studied until now. In this study we evaluated the LOC in a population of patients with FLE and studied the relationship between changes in synchrony and degree of LOC. Methods: 24 patients undergoing stereoelectroencephalography (SEEG) during pre-surgical evaluation of FLE were studied. The LOC intensity was scored using the Consciousness Seizure Scale (CSS). For each studied seizure ( n = 52), interdependencies between signals recorded from 5 brain regions were estimated as a function of time by using non-linear regression analysis ( h 2 coefficient). Results: Seizures were divided into 3 groups according to the CSS scale: group A (no LOC) with a score ⩽2, group B (intermediate or partial LOC) with a score ranging from 3 to 5, and group C (maximal LOC) with a score ⩾6. The majority of seizures in FLE patients disclosed significant LOC, particularly for patients with prefrontal lobe seizures. Mean correlation values were significantly different between groups A and C ( p < 0.001), the maximal values of synchrony being observed in group C. Differences were significant for interaction affecting the external prefrontal cortex ( p = 0.004) ( p = 0.01) and the parietal cortex. In addition, a significant correlation was found between CSS scores and correlations values ( h 2 ) of the prefrontal and the parietal region but not with the premotor cortex. Conclusions: This study indicates that in FLE, prefrontal seizures frequently alter consciousness. As in other focal seizures, LOC appears to be related to changes in synchrony in prefrontal and parietal associative cortices. Significance: LOC in FLE is frequent and as in other focal epilepsies is related to an alteration of prefrontal–parietal network.